Pneumatosis intestinalis an increasingly common radiological finding, benign or life-threatening? A case series. (18th February 2015) - Blair, Holly Alison; Baker, Richard; Albazaz, Raneem
Abstract : This case series reviews two cases where elderly patients were found to have pneumatosis intestinalis on imaging. The two clinical presentations differed from one another, however, both were managed conservatively to good effect. In case one the patient presented with abdominal pain, a change in bowel habit and weight loss. In case two the patient presented with problematic diarrhoea, reduced oral intake, lethargy and weight loss. Both patients were haemodynamically stable and neither had an abnormal abdominal examination. Case 2 was started on oral metronidazole and by day 11 of treatment there was resolution of the pneumatosis on her abdominal X-ray and her diarrhoea had settled. These two cases illustrate the benefit of conservative management and avoidance of unnecessary surgical intervention in primary pneumatosis intestinalis. However, it is important to distinguish between these benign causes of pneumatosis intestinalis and those which are life-threatening in which surgery may be necessary.